ANALISIS FILOGENETIK GEN atpA PADA GENUS Oryza MENGGUNAKAN PERANGKAT LUNAK MEGA DENGAN PENDEKATAN NEIGHBOR-JOINING - Zacki Rafila; Violita; Afifatul Achyar (Universitas Cokroaminoto Palopo, 2026)
This study aims to analyze the phylogenetic relationship of the atpA gene in the genus Oryza using Molecular Evolutionary Genetics Analysis (MEGA) software. The atpA gene, which plays a role in ATP synthesis in chloroplasts, was selected because of its relatively conserved nature and relevance in plant molecular evolution studies. The atpA gene sequences from 13 Oryza species were obtained from the NCBI GenBank database and analyzed using the Neighbor-Joining (NJ) method with the Kimura 2-Parameter model to reconstruct the phylogenetic tree. The reliability of the tree branches was tested through a bootstrap analysis of 10,000 repetitions. The results showed a pattern of kinship consistent with existing taxonomic classifications, in which Oryza sativa tended to form a single clade with Oryza rufipogon as its closest ancestor, while wild species such as Oryza punctata and Oryza officinalis formed a separate and more divergent clade. The relatively high bootstrap values at several branches indicate the reliability of the phylogenetic inferences generated. These findings reinforce the hypothesis that rice domestication involved wild species genetically close to cultivated species and suggest that the atpA gene has the potential to be used as an effective molecular marker in phylogenetic studies of the genus Oryza.